Pengaruh Campuran Pelet Kudzu Dengan Karbohidrat Terhadap Protein Total, Urea, Glukosa dan Kolesterol Darah Domba Ekor Tipis - Muhamad - Ramdhan; Iin Susilawati; Novi Mayasari (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
This research aimed to determine blood protein total, blood urea, blood glucose and blood cholseterol on thin tail rams which is administered kudzu pellet with readily available carbohydrates. Experimental method used completely randomize design. The data was analyzed through Anova and Duncan’s Multiple Range Test. Twenty four local rams are divided into four dietary treatment, namely RK = 50 % napier grass + 50 % concentrate, KD = 50 % napier grass + 25 % kudzu pellet with rice bran + 25 % concentrate, KM = 50 % napier grass + 25 % kudzu pellet with molasses + 25 % concentrate, KG = 50 % napier grass + 25 % kudzu pellet dried cassava + 25 % concentrate. Each treatment was replicated six times. Administering dried cassava (KG) in kudzu showed significance (P<0,05) blood glucose in thin-tailed ram compared to control dietary (RK) and bran rice kudzu pellet (KD) based on table 2. Administering dried cassava (KG) and molasses (KM) in kudzu pellet provided similar response (Table 2) on blood glucose level. Blood cholesterol level decreased along with the duration of treatment (Table 2) during 60 days compared before treatment. The result showed that duration of treatment made a significant decrease (P<0,05) (Table 2) on blood cholesterol in rams. Blood total protein declined when the treatment was administered during 60 days. The result explained that duration of treatment is significant (P<0,05) to decrease blood total protein level on rams (Table 2). The blood urea level of this research showed that the duration of treament is significant (P<0,05) to increase blood urea level on thin-tailed rams (Table 2). Blood urea level on each treatment was range between 31,23 mg/dL – 34,57 mg/dL. This result explained that the increase of blood urea level showed a significant difference (P<0,05) when diet treatments interacted with the duration of treatment. The conclusion of this research was administering dried cassava (KG) and molasses (KM) in kudzu pellet increase blood glucose level, stabilized blood total protein, urea and cholesterol in thin-tailed rams. However, the protein balance in thin-tailed rams diet on different age should be considered in order to support the growth. Keywords: Kudzu, Blood Urea, Blood Glucose, Blood Protein Total, Blood Cholesterol